Technical and legal instruments to support the adoption of the public expenditure and financial responsibility program (PEFA) in the evaluation of municipal public finance management (Research, Society and Development, 2021)
Public Administration has received several contributions regarding the use of tools that shape Public Financial Management (PFM). The Public Expenses and Financial Responsibility Program (PEFA) assesses the quality of PFM at all levels of Public Administration, considering information and data contained in the planning and budget instruments. PEFA allows the revelation of strengths and weaknesses within the PFM. The objective of this study was to identify and discuss how the legal and technical instruments regulated since the 1988 Constitution provide support for the adoption of the PEFA Framework program for the evaluation of municipal Public Financial Management in the period from 2016 to 2020. The method used for the construction of this research is Bibliographic Review of Literature. The research allowed to identify that these instruments complement each other and that PEFA recognizes and points out the evolution of the reforms presented by the governments and the results obtained through the plan of actions implemented to improve the PFM. In addition, laws designed to assist in the regulation of planning and budgeting in order to direct good governance and transparent management are foundations for the PEFA Framework program method to be used in the evaluation of municipal PFM.